Perbandingan Efektivitas dan Keamanan terhadap Kejadian Patent Ductus Arteriosus pada Bayi Prematur - Wijaya, Diana (Jurnal MedScientiae, 2024)
Patent ductus arteriosus (PDA) is a ductus arteriosus that cannot be closed spontaneously after birth due to failure of physiological closure of the fetal ductus. The initial pharmacological treatment for PDA is ibuprofen. The other drugs that can be given, such as paracetamol which has the same role as ibuprofen by inhibiting the synthesis of prostaglandins. Several studies have compared the effectiveness and side effects of the two drugs and obtained different results have shown that paracetamol cannot be used in all premature infants. This literature review was conducted to determine the comparison of paracetamol and ibuprofen in premature infants diagnosed with patent ductus arteriosus. From the analysis of 15 journals, the comparison of the effectiveness of paracetamol and ibuprofen in premature infants has the same effectiveness and there is no statistically significant difference. But the effectiveness of ibuprofen is much better in premature infants with very low birth weight (VLBW) and extremely low birth weight (ELBW) infants than paracetamol. The adverse effects that are often caused by ibuprofen are gastrointestinal bleeding, thrombocytopenia, increased BUN levels, increased serum creatinine levels, increased incidence of AKI, hyperbilirubinemia, and oliguria. Meanwhile, other side effects such as BPD, IVH, NEC, ROP, sepsis, SGOT and SGPT levels and death were not found to be statistically significant differences in the two drugs.